Occurrence and diversity of thermophilic sporeformers in French dairy powders. (February 2021) - Delaunay, Louis; Cozien, Emeline; Gehannin, Pierre; Mouhali, Nassim; Mace, Sabrina; Postollec, Florence; Leguerinel, Ivan; Mathot, Anne-Gabrielle
Abstract: This study reports the prevalence of sporeforming bacteria and contamination levels of a variety of powdered dairy products from cows', ewes', goats' and mares' milk produced in France. The concentration of mesophilic spores, thermophilic spores and highly heat-resistant thermophilic spores was assessed in 61 dairy powders. Thermophilic spore concentration was highly variable between powders, likely due to the different manufacturing processes used for transforming milk into dairy powders. The different stages of processing, particularly heat treatment close to 55 °C had a strong impact on selection of thermophilic bacteria contaminating dairy powders. For some products, thermophilic spore counts were as high as 5.89 log TSC g −1 . Of the 313 thermophilic isolates selected, 93.3% belonged to the species Geobacillus stearothermophilus (43.5%), Bacillus licheniformis (30.0%) and Anoxybacillus flavithermus (19.8%). These results confirm the presence of the three majority species reported worldwide.